Income and happiness across Europe: do reference values matter? - Guglielmo Maria Caporale; Yannis Georgellis; Nicholas Tsitsianis; Ya Ping (Center for Economic Studies and ifo Institute (CESifo), 2007)
Using data from the European Social Survey (ESS), we examine the link between income and subjective well-being. We find that, for the whole sample of nineteen European countries, although income is positively correlated with both happiness and life satisfaction, reference income exerts a negative effect on individual well-being, a result consistent with the relative utility hypothesis. Performing separate analyses for some Eastern European countries, we also find some evidence of a tunnel effect', in that reference income has a positive impact on subjective well-being. Our findings support the view that in environments with stable income and employment, reference income serves as a basis for social comparisons, whereas in relatively volatile environments, it is used as a source of information for forming expectations about future status.
Keywords: I31; 330; comparison income; reference groups; happiness; life satisfaction; Einkommensverteilung; Lebensqualität; Lebenszufriedenheit; Statistisches Auswahlverfahren; Schätzung; Europa